A bibliometric analysis of research trends of artificial intelligence in the treatment of autistic spectrum disorders - Zhang, Shouyao; Wang, Shuang; Liu, Ruilu; Dong, Hang; Zhang, Xinghe; Tai, Xiantao (Frontiers in Psychiatry, 2022)
Objective: The application of artificial intelligence (AI) in autism spectrum disorder (ASD) has attracted more and more attention. However, there is no quantitative analysis of visual literature on the use of artificial intelligence in the treatment of autism. By using the analysis method of bibliometrics, this study objectively analyzes the current research trends, research hotspots, main research countries, institutions and their cooperative relations in this field, and presents them in the form of knowledge graph, in order to provide basis for future research. Methods: The literatures related to the treatment of ASD with AI from 1995 to April 2022 were searched from Web of Science database and Pubmed database. CiteSpace, VOSviewer, Pajek and Scimago Graphica are used to extract relevant countries, institutions, authors, journals, references and keywords in this field, and the results are analyzed comprehensively. Results: A total of 448 articles were included. Over the past 26 years, the total number of publications has shown an increasing trend. The most productive countries in this area are the United States. Vanderbilt Univ is the most influential research institution. The authors with the greatest contributions are Warren,Zachary,Sakar, Nilanjan and Swanson,Amy. The journal with the most prolific and the highest cited frequency is J Autism Dev Disord, and the highest cited and co-cited literatures are Dautenhahn (2007) and Scassellati B (2012). The keyword "Children" has the highest centrality, and "Artificial Intelligence", "Brain Computer Interface" and "Humanoid Robot" are the hot keywords of AI in the treatment of ASD. Conclusion: The research of ASD has shown a global participation trend led by some countries and institutions. Children are the objects of ASD that researchers focus on. The social function of ASD patients is the difficulty for researchers to overcome. Robots are the most common artificial intelligence technology used in ASD. Wearable devices and brain-computer interface technology are potential methods for ASD treatment. Facing the ethical problems and technical barriers caused by robots is the direction of further research and exploration in the future.